AB0278 Are There Differences in Basal Comorbidities between Rheumatoid Arthritis Patients Treated with Abatacept and Those Treated with Tumor Necrosis Factor Inhibitors?. (15th July 2016) - Hernández, M.V.; Sánchez-Piedra, C.A.; Inciarte-Mundo, J.E.; Sánchez-Alonso, F.; Manero-Ruiz, F.J.; Cuende, E.; Rosellό Pardo, R.; Pérez-Pampín, E.; Rodríguez-Lozano, C.; Vela-Casasempere, P.; Diaz-Torne, C.; Sanmartí, R.; et al.
Abstract : Background: Rheumatoid arthritis (RA) patients frequently report concomitant comorbidities that could worsen their prognosis. Tumour necrosis factor inhibitors (TNFi), the most common biological agents used, have shown efficacy in RA patients, although use in RA patients with certain comorbidities warrant caution (1). Abatacept, a biologic agent with a different mechanism of action, inhibiting the co-stimulation of T-lymphocyte, has demonstrated differentiated safety profile (2), that could influence the biological agent prescribed in RA patients with some associated comorbidities Objectives: To analyse differences in the frequency of baseline comorbidities in RA patients treated with abatacept compared with those treated with TNFi Methods: Patients with RA recruited into the BIOBADASER 2.0 register from January 2008 to December 2014 and treated with abatacept or TNFi with comorbidities were selected. Comorbidity was defined as ≥1 of the following at initiation of biological therapy: ischemic heart disease; malignancy (except lymphoma); diabetes; chronic pulmonary obstructive disease (CPOD); smoking; hypercholesterolemia; hypertension; heart failure; renal failure; lymphoma; osteoporosis; Epstein Barr, hepatitis B or C virus infection; and others. We analysed the frequency of each comorbidity, and differences in the rate of baseline comorbidities in the two groups were compared using t-test Results: From January 2008 to December 2014, 640 and 252 RA patients treated respectively with TNFi or abatacept were included in the BIOBADASER 2.0 register, of whom 51.6% had ≥1 comorbidity at baseline. Frequencies for every basal comorbidity described are shown in Table 1 . There was a significantly higher rate of heart failure in abatacept than in TNFi patients. Other comorbidities showed no significant differences. Conclusions: RA patients treated with abatacept had a higher baseline rate of concomitant heart failure compared with patients treated with TNFi, probably reflecting different recommendations on biological use. Even though abatacept has demonstrated a differentiated safety profile, overall no differences in other baseline comorbidities were found between groups References: Singh et al. Arthritis Rheum 2016;68:1–26. Singh et al. Cochrane Database Syst Rev. 2011;16:CD008794 Disclosure of Interest: None declared